2015
DOI: 10.1038/srep18295
|View full text |Cite
|
Sign up to set email alerts
|

Diiron centre mutations in Ciona intestinalis alternative oxidase abolish enzymatic activity and prevent rescue of cytochrome oxidase deficiency in flies

Abstract: The mitochondrial alternative oxidase, AOX, carries out the non proton-motive re-oxidation of ubiquinol by oxygen in lower eukaryotes, plants and some animals. Here we created a modified version of AOX from Ciona instestinalis, carrying mutations at conserved residues predicted to be required for chelation of the diiron prosthetic group. The modified protein was stably expressed in mammalian cells or flies, but lacked enzymatic activity and was unable to rescue the phenotypes of flies knocked down for a subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…This could be verified by using an enzymatically incapacitated version of the enzyme expressed at the same high level as daGAL4-driven UAS-AOX. A previously generated control line transgenic for a mutated (inactive) AOX variant would not suffice, since the transgene was expressed at a much lower level (Andjelković et al, 2015). However, the expression of neither cytosolically expressed GFP (Saari et al, 2018) nor the GAL4 transcription factor caused developmental failure in low-nutrient medium, making it unlikely that a general proteotoxic effect is responsible.…”
Section: Mechanism Of Developmental Failure Of Aox-expressing Fliesmentioning
confidence: 99%
“…This could be verified by using an enzymatically incapacitated version of the enzyme expressed at the same high level as daGAL4-driven UAS-AOX. A previously generated control line transgenic for a mutated (inactive) AOX variant would not suffice, since the transgene was expressed at a much lower level (Andjelković et al, 2015). However, the expression of neither cytosolically expressed GFP (Saari et al, 2018) nor the GAL4 transcription factor caused developmental failure in low-nutrient medium, making it unlikely that a general proteotoxic effect is responsible.…”
Section: Mechanism Of Developmental Failure Of Aox-expressing Fliesmentioning
confidence: 99%
“…Superoxide levels increased under hypoxic conditions in WT but not in AOX PASMC. To validate this finding, we expressed either native AOX or a catalytically inactive mutant AOX (20) in WT mouse PASMC. Only the inactive mutant AOX showed a hypoxia-dependent increase in superoxide ( Fig.…”
Section: Aox Inhibits Hypoxia-induced Mitochondrial Superoxide Releasmentioning
confidence: 96%
“…AOX was able to rescue completely or at least substantially these phenotypes, depending on their severity or tissue‐specificity. Later, we showed that a catalytically inactive form of this alternative enzyme was unable to rescue the deleterious effects of complex IV knockdown (Andjelković et al, ). A replica of the developmental assays demonstrating AOX rescue of complex IV depletion is shown in Figure for illustration purposes.…”
Section: Effects Of Alternative Oxidase Expression In Model Organismsmentioning
confidence: 99%
“…A catalytically inactive form of AOX (indicated as mut ) is unable to provide such developmental rescue. More details about the fly lines used here and other complex IV defects rescued by AOX are shown in Kemppainen et al () and Andjelković et al ().…”
Section: Effects Of Alternative Oxidase Expression In Model Organismsmentioning
confidence: 99%